2002
DOI: 10.1097/00006534-200212000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Common Craniofacial Anomalies: The Facial Dysostoses

Abstract: After studying this article, the participant should be able to: 1. Understand the etiology and pathogenesis of facial dysostosis syndromes. 2. Recognize and classify common facial dysostoses. 3. Understand the different management plans for the reconstruction of facial dysostoses. The wide spectrum of craniofacial malformations makes classification difficult. A simple classification system allows an overview of the current understanding of the etiology, assessment, and treatment of the most frequently encounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 57 publications
0
34
0
2
Order By: Relevance
“…Preaxial upper limb defects point to the AFD Nager phenotype, whereas postaxial limb defects point to the Genée-Wiedemann or Miller syndrome [Opitz et al, 1993[Opitz et al, , 1998]. Diagnostically relevant are also Treacher CollinsFranceschetti syndrome, Robin sequence, and Stickler syndrome [Opitz et al, 1993;Witkowski et al, 1995;Hunt and Hobar, 2002]. The diagnosis should be based on the type of limb malformations [Witkowski et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preaxial upper limb defects point to the AFD Nager phenotype, whereas postaxial limb defects point to the Genée-Wiedemann or Miller syndrome [Opitz et al, 1993[Opitz et al, , 1998]. Diagnostically relevant are also Treacher CollinsFranceschetti syndrome, Robin sequence, and Stickler syndrome [Opitz et al, 1993;Witkowski et al, 1995;Hunt and Hobar, 2002]. The diagnosis should be based on the type of limb malformations [Witkowski et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of the NAFD varies extremely between affected individuals, ranging from severe malformations and intruterine death to very mild forms, which may easily escape correct diagnosis [Opitz et al, 1993;David et al, 1996;Fryns et al, 1996;Hunt and Hobar, 2002]. The main facial characteristics for the pathological-anatomical diagnosis are mandibular hypoplasia, velar hypoplasia, and zygomatic bone hypoplasia [Opitz et al, 1993[Opitz et al, , 1998Hunt and Hobar, 2002].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Goldenhar syndrome is part of the oculo-auriculovertebral spectrum and is recognized as a syndrome because, in addition to the mandibulofacial dysostosis, there are other vertebral anomalies and epibulbar dermoids. 2 The expression of this pathology is highly variable, with 70% of patients suffering unilateral involvement and those that have bilateral conditions will be more severely affected on one side than the other. 3 Studies with animal models have suggested that Goldenhar syndrome appears due to a vascular disruption in the embryo, at 35 to 40 days gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Hemifacial microsomia is a complex congenital craniofacial malformation, displaying a wide phenotype with no universally agreed minimal diagnostic criteria 2,3 . It involves asymmetrical hypoplasia of the facial skeleton and associated soft tissues.…”
mentioning
confidence: 99%